Determinant Factors Of Loyalty Mediated By Hospital Patient Satisfaction - Sarwo Edy Handoyo; Mutiara Sri Rahayu (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of corporate image and service quality on patient loyalty, with patient satisfaction as a mediating variable, at the Kota Bekasi Regional General Hospital (RSUD) in Bekasi City. This RSUD is a public health facility that faces challenges in maintaining and increasing patient satisfaction and loyalty amidst fluctuations in service quality and patient complaints. A quantitative research method with an explanatory approach was used, with data analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM). A total of seven hypotheses were tested in this study. The results showed that corporate image and service quality have a positive and significant influence on patient satisfaction. In addition, corporate image also has a positive and significant influence on patient loyalty, and patient satisfaction has a positive and significant influence on patient loyalty. Another important finding is that patient satisfaction is able to mediate the influence of corporate image on patient loyalty significantly. However, service quality does not have a significant direct influence on patient loyalty, and patient satisfaction is also unable to significantly mediate the influence of service quality on patient loyalty.